2022
DOI: 10.21037/tau-22-190
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease is associated with worse sexual function: a systematic review and meta-analysis

Abstract: Background: Several studies report that sexuality is often affected by inflammatory bowel diseases (IBD).The aim of this meta-analysis was to investigate the association between IBD and sexual function.Methods: A literature search was conducted in PubMed, Web of Science, and EMBASE databases (up to September 1, 2020). Scores of sexual functions with a standard deviation and odds ratio (OR) or relative risk (RR) with a 95% CI were used to analysis the association between IBD and sexual function.Results: Eleven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In the IMPACT study ( 37 ), a large survey conducted across Europe aimed at understanding the impact of IBD on patients’ lives, 40% of patients reported that disease activity negatively affected intimate relationships. In a recent meta-analysis conducted by Chen et al ( 38 ) on 11 studies, the risk of SD in male patients with IBD was significantly higher than in individuals without IBD (OR = 1.61, 95% CI: 1.17 to 2.23, p = 0.004). Similarly, female patients with IBD had a significantly higher risk of SD compared to healthy controls (OR = 2.28, 95% CI: 1.54 to 3.37, p < 0.0001).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the IMPACT study ( 37 ), a large survey conducted across Europe aimed at understanding the impact of IBD on patients’ lives, 40% of patients reported that disease activity negatively affected intimate relationships. In a recent meta-analysis conducted by Chen et al ( 38 ) on 11 studies, the risk of SD in male patients with IBD was significantly higher than in individuals without IBD (OR = 1.61, 95% CI: 1.17 to 2.23, p = 0.004). Similarly, female patients with IBD had a significantly higher risk of SD compared to healthy controls (OR = 2.28, 95% CI: 1.54 to 3.37, p < 0.0001).…”
Section: Methodsmentioning
confidence: 97%
“…The prevalence of SD in female patients with IBD tends to be higher than in male patients, with rates ranging from 21.1 to 48.2% in men and from 51.0 to 73.7% in women ( 38 ). The reason behind this finding is unclear; however, women may be more concerned than men about intimacy, sexual performance and relationship issues because of their disease.…”
Section: Methodsmentioning
confidence: 99%